Teacher educators' task perception and its relationship to professional identity and teaching practice. (May 2021) - Richter, Eric; Brunner, Martin; Richter, Dirk
Abstract: We assessed teacher educators' task perception and investigated its relationship with components of their professional identity and their teaching practice. Using data from 145 teacher educators, two different task perceptions were found: transmitters and facilitators. Teacher educators who were categorized as facilitator tend to demonstrate higher levels of self-efficacy, job satisfaction, constructivist beliefs about teaching and learning and use more effective teaching strategies. The findings demonstrate that teaching practices of teacher educators are rooted in their professional identity. Highlights: One of the first quantitative studies on teacher educators' professional identity. Valid and empirically reliable measurement of teacher educators' task perception. We distinguish between teacher educators as facilitators and transmitters. Facilitators demonstrate increased self-efficacy. Teacher educators' task perception is related to the quality of teacher training.